Synthesis of a Bone-Targeted Bortezomib with In Vivo Anti-Myeloma Effects in Mice - Hua Wang; Lifeng Xiao; Jianguo Tao; Venkat Srinivasan; Brendan F. Boyce; Frank H. Ebetino; Babatunde O. Oyajobi; Robert K. Boeckman; Lianping Xing (MDPI AG, 2018)
Multiple myeloma (MM) is the most common cancer affecting the bone and bone marrow and remains incurable for most patients; novel therapies are therefore needed. Bortezomib (Btz) is an FDA-approved drug for the treatment of patients with MM. However, its severe side effects require a dose reduction or the potential discontinuation of treatment. To overcome this limitation, we conjugated Btz to a bisphosphonate (BP) residue lacking anti-osteoclastic activity using a novel chemical linker and generated a new bone-targeted Btz-based (BP-Btz) proteasome inhibitor. We demonstrated that BP-Btz, but not Btz, bound to bone slices and inhibited the growth of MM cells in vitro. In a mouse model of MM, BP-Btz more effectively reduced tumor burden and bone loss with less systemic side effects than Btz. Thus, BP-Btz may represent a novel therapeutic approach to treat patients with MM.